Negative feedback as an obligatory antecedent to the estradiol-induced luteinizing hormone surge in ovariectomized pigs - Kesner, J S; Price-Taras, E A; Kraeling, R R; Rampacek, G B; Barb, C R (Biology of reproduction, 1989)
In ovariectomized pigs, estradiol treatment induces a preovulatory-like luteinizing hormone (LH) surge, but only after serum LH concentrations are suppressed for 48 h. This inhibition of LH release is attributable in large part to inhibition of gonadotropin-releasing hormone (GnRH) release. The present report examines the dependency of the estradiol-induced LH surge on this preceding phase of negative feedback. Ten ovariectomized gilts were given an i.m. injection of estradiol benzoate (10 micrograms/kg BW). Beginning at the time of estradiol treatment, 5 of these gilts received 1-microgram GnRH pulses i.v. every 45 min for 48 h, i.e. during the period of negative feedback. The remaining 5 control gilts received comparable infusions of vehicle. Estradiol induced the characteristic biphasic LH response in control gilts. On the other hand, the inhibitory LH response to estradiol was prevented and the ensuing LH surge was blocked in 4 of the 5 gilts given GnRH pulses during the negative feedback phase. These results indicate that suppressing release of GnRH and/or LH is an important antecedent to full expression of the LH surge in ovariectomized pigs. Assimilation of this observation with the existing literature provides novel insights into the neuroendocrine control of LH secretion in castrated and ovary-intact gilts.